Movimiento político compromiso ciudadano de la ciudad de Medellín : entre utopía cívica y pragmática política (2013)
ABSTRACT: This work deals with the origins, evolution and dissolution of the political movement Compromiso Ciudadano (Citizen Commitment), which ruled the city of Medellin for two consecutive periods from 2004 to 2011. The article progress in: i) showing how great part of the ‘success’ –and other less publicized results– of the recent Government in the city of Medellin are due in large part to a double collective process: a) social movements and social resistance before fear and violence and b) comprehensive and creative social interaction between different sectors of social classes that articulated and redefined the utopic and the pragmatic of the political action in the City Government, particularly in its versions of democratic left and liberal republicanism; and ii) indicating the difficulties, limits and potential of both rationalities (utopic and pragmatic) in building a democratic city and urban development political project in a national context of political realignments that, eventually, lead to the spread of this movement members around the different center-left and center-right offerings that have always surrounded it.